Orthopaedic neurology : a diagnostic guide to neurologic levels - Hoppenfeld, J. D. (Jon-David); Hoppenfeld, Stanley, 1934-2020 (Wolters Kluwer, 2018)
"Since its original publication, Orthopaedic Neurology: A Diagnostic Guide to Neurologic Levels has distinguished itself as a clearly written, uniquely focused text sought after by practitioners and trainees in orthopaedics, neurosurgery, physical medicine and rehabilitation, pain medicine, anesthesiology, neurology, and nursing, as well as primary care specialties. The second edition retains this standard of excellence while providing thorough updates in medical illustration, teaching techniques, and new approaches to the diagnosis and treatment of patients with spinal cord injuries. Now in vibrant full color, it offers a distinctive and practical combination of anatomy, the physical exam, and clinical pearls, highly readable and abundantly illustrated. Features:Discusses the diagnosis of neurologic levels according to common denominators, and combines them with the basic principles of neurology to assist in the appraisal of spinal cord and nerve root problems. Presents classic original drawings now carefully colorized for optimal visual reference, and additional drawings added as necessary. Corresponding radiographic imaging (predominantly MRI and CT) have also been added. Each chapter first covers basic neurologic information, then provides clinical significance by applying it to the diagnosis of the more common neurologic pathologies. Ideal for those who wish to understand more clearly the clinical concepts behind neurologic levels, moving systematically from concept to practice, and from general rules to specific applications."--Provided by publisher